Migration Status and Smoking Behaviors in Later-Life in China—Evidence From the China Health and Retirement Longitudinal Study (CHARLS) - Hou, Bo; Nazroo, James; Banks, James; Marshall, Alan (Frontiers in Public Health, 2018)
Background: China is the biggest consumer of tobacco in the world, with a high prevalence of smoking especially among men. Along with the rapid demographic change in China, the burden of diseases attributable to health behaviors, particularly smoking is steadily increasing. So, smoking has become a major risk factor for mortality in China. Smoking behaviors may be related to migration processes, as a result of both who migrates and post-migration experiences related to socioeconomic position, stress and acculturation. Existing studies that have examined smoking and migration in China have, however, only focused on temporary rural-to-urban migrants and focused on relatively younger migrants. This paper examines the association between smoking behaviors and a comprehensive assessment of migration status in later-life in China. Methods: Using the China Health and Retirement Longitudinal Study (CHARLS), a nationally representative dataset, this paper studies smoking behaviors of rural-to-urban migrants, urban-to-urban migrants, rural return migrants, and urban return migrants. We compare them with corresponding non-migrant groups in both rural and urban locations in China. Using a model that controls for demographic factors, early-life circumstances, socioeconomic factors, and factors related to migration, we examine both the decision to start smoking and the decision to quit smoking. In addition, we also address pre-migration selection in our analyses. Results: The results show rural-to-urban migrants are no more likely to start smoking compared with rural non-migrants, but they are more likely to quit smoking. While urban-to-urban migrants are more likely to start smoking compared with urban non-migrants, this effect is explained by the factors we include in the full model. Urban-to-urban migrants are, however, less likely to quit smoking. Moreover, both rural return migrants and urban return migrants seem to be more likely to start smoking and less likely to quit smoking compared with non-migrant groups. Conclusion: There are strong associations between migration status and later-life smoking behaviors in China; these associations vary greatly according to different migration status and point to populations and factors that public health activities should focus on.